The Nature Support Model for Dementia: a conceptual idea for green nursing home environments designed to support well-being throughout the last stages of dementia - Lygum, Victoria Linn; Mathiasen, Nanet; Frandsen, Anne Kathrine (Frontiers in Psychology, 2025)
Dementia is one of the world’s greatest public health challenges. An increasing number of studies point to contact with nature in the form of green views and stays in green environments as a non-pharmacological way of supporting the well-being of persons with dementia. This article introduces the Nature Support Model for Dementia, a conceptual idea that can be used to design green environments at nursing homes for people with dementia intended to support the user’s health and well-being. The model is evidence-based and reposes on studies on user specific design of green environments. Furthermore, it builds on existing conceptual models for the design of supportive green environments. It caters to nursing home residents in the final stages of dementia decline. It considers their increasing needs for assistance and meets the needs for safety and security. The model was developed in connection with an evidence-based design process resulting in an architectural proposal for a nursing home. A presentation of this proposal illustrates how the model can be used in practice to facilitate architectural programming and the design of green nursing home environments intended to be supportive.